(untitled) (Journal of the Management Sciences, 2024)
This study examined green resources initiative and sustainability of federal universities in Nigeria. Four selected measures of green resources were exploited to determine their relationships on sustainability. The researcher formulated four specific objectives and adopted a descriptive survey research design. Population of the study comprised 550 employees selected from ten federal universities in Nigeria. The researcher utilized purposive sampling technique and Taro Yamane’s formula was employed to determine the sample size at 232.Primary data was collected through a structured questionnaire. Two hundred and thirty two (232) copies of questionnaire were returned as valid after distributions. Spearman rank correlation was used to test the hypotheses and descriptive statistics applied in the analysis of research questions. The findings revealed a positive significant relationship between green resources and sustainability of federal universities in Nigeria. The researcher concluded that green resources influence sustainability and recommended that universities should introduce green change like recycling of papers and use software to capture all the degree results necessary for sustainability performance.